Variations of Dermatological Findings in New-Borns of a Community Hospital in Nepal - Shrestha, Asim; Shrestha, Smriti (Journal of Nepal Paediatric Society, 2018)
Introduction: Skin manifestations are common in neonates. The prevalence of skin changes and their association with neonatal and maternal factors are not adequately documented in Nepal. It is important to differentiate common benign skin lesions from infrequent skin changes that cause morbidity, requiring medical management. The objectives of this study were to determine the pattern of skin lesions in new-borns and their association with maternal and neonatal variables. Material and Methods: This was a prospective, cross-sectional study conducted in obstetric unit of the hospital from December 2016 to May 2017. Outborn babies and babies shifted to NICU were excluded. Results: A total of 935 new-borns were examined. The commonest skin lesions were Mongolian spot (66.7%), Erythema toxicum (46.6%), Milia (44.4%), Epstein pearls (26.4%) and Salmon patch (11.9%). Mothers aged 35 years or older (63.6%) had statistically significant association with Erythema toxicum (p=0.01). Erythema toxicum was more in primiparity, term pregnancy and caesarean section delivery. Milia was associated with male babies. Salmon patch was seen more in term pregnancy. Congenital melanocytic nevus, haemangioma and port-wine stain were noted in three, two and one new-borns respectively, which alter morbidity and hence are important to diagnose in time. Conclusion: We found that 93.8% of neonates had at one or more skin lesions. The majority of skin lesions were benign and transient. Erythema toxicum was seen commonly in mothers aged 35 and more. Salmon patch was seen more in term pregnancy.